Effect of Ce substitution on the structural and magnetic properties of Nd2Fe14B. (November 2020) - Lin, Zhongchong; Zha, Liang; Wang, Fanggui; Liu, Zhou; Wu, Rui; Yang, Jie; Xue, Mingzhu; Yang, Wenyun; Tian, Guang; Ma, Xiaobai; Qiao, Liang; Franz, Alexandra; et al.
Abstract: The effect of Ce substitution on the structural and magnetic properties of (Nd1-δ Ceδ )2 Fe14 B (0 < δ < 1) series was systematically studied using neutron diffraction, 57 Fe Mössbauer spectroscopy and X-ray magnetic circular dichroism (XMCD). An anomaly in the lattice parameters was observed in a sample with composition in the range of 0.2 < δ < 0.4, where a phase separation happens and the 2:14:1 isostructural dual-main-phases (IDMPs) appear. Outside this composition range, Ce shows a preferential occupation at the 4g site than the 4f site and a preferable Ce 3+ valence state. The average magnetic moments of Nd/Ce and Fe atoms decrease with the increasing of δ. The magnitude of the Fe moments at non-equivalent sites is related to several factors, such as the Fe coordination number, the Wigner-Seitz cell volume, and the Boron atom effect. These results reveal the microscopic mechanisms for the structural and magnetic properties of Ce-substitution Nd2 Fe14 B, providing perspective on developing the next-generation low-cost and high-performance permanent magnetic materials. Graphical abstract: Image, graphical abstract